2020
DOI: 10.1097/md.0000000000022606
|View full text |Cite
|
Sign up to set email alerts
|

Differences in human immunodeficiency virus-1C viral load and drug resistance mutation between plasma and cerebrospinal fluid in patients with human immunodeficiency virus-associated cryptococcal meningitis in Botswana

Abstract: To determine effects of cryptococcal meningitis (CM) on human immunodeficiency virus (HIV)-1C cerebrospinal fluid (CSF) viral escape, CSF/plasma viral discordance, and drug resistance mutation (DRM) discordance between CSF and plasma compartments, we compared CSF and plasma viral load (VL) and DRMs in individuals with HIV-associated CM in Botswana. This cross-sectional study utilized 45 paired CSF/plasma samples from participants in a CM treatment trial (2014–2016). HIV-1 VL was determined and HIV-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
3
1
Order By: Relevance
“…In this study that compared CSF HIV-1 VL versus plasma HIV-1 VL in individuals with HIV-associated cryptococcal meningitis, we observed a substantial proportion of individuals experiencing CSF viral escape (32.3% with day 1 samples, 25.0% with day 7 and 3.0% with day 14 samples). This is higher than our previous study which observed a very low prevalence (2.9%) of CSF viral escape among 34 individuals with HIV-associated cryptococcal meningitis [ 25 ]. This may be because the previous study analysed a combination of samples collected on either day 3, 7, or 14 post-initiation of antifungal therapy, potentially missing episodes of CSF viral escape which only occurred around baseline.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…In this study that compared CSF HIV-1 VL versus plasma HIV-1 VL in individuals with HIV-associated cryptococcal meningitis, we observed a substantial proportion of individuals experiencing CSF viral escape (32.3% with day 1 samples, 25.0% with day 7 and 3.0% with day 14 samples). This is higher than our previous study which observed a very low prevalence (2.9%) of CSF viral escape among 34 individuals with HIV-associated cryptococcal meningitis [ 25 ]. This may be because the previous study analysed a combination of samples collected on either day 3, 7, or 14 post-initiation of antifungal therapy, potentially missing episodes of CSF viral escape which only occurred around baseline.…”
Section: Discussioncontrasting
confidence: 73%
“…This study aims to determine the prevalence of CSF HIV-1 viral escape and evaluate the HIV-1 VL trajectories in individuals treated for HIV-associated cryptococcal meningitis. Compared to our previous study which was done prior to the introduction of the “treat all strategy” [ 25 ], the current study explores CSF viral escape in a cohort where almost half of the participants were ART-experienced. This study will also advance our understanding of CSF viral escape in the context of antifungal treatment and their impact on CSF and plasma HIV-1 VL over time.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations reported were also often polymorphic or a single drug resistance mutation, unlikely to result in clinically significant difference in drug susceptibility. Although CSF escape and discordant HIV drug resistance can occur, people with HIV can also have compartmentalized drug resistance without CSF escape [58]. CSF HIV viral load testing may nevertheless be useful in patients with HAND as it can identify those who may have ongoing viral replication in the CNS and who are in need of an ART regimen with improved CPE [47,49,50].…”
Section: Degree Of Mixingmentioning
confidence: 99%
“…Nonetheless, plasma and CSF drug resistance tests have been used by some investigators to inform HIV therapy decisions [54]. Several recent studies have reported individual cases of discordant HIV drug resistance between CSF and blood, sometimes detecting mutations in blood plasma but not CSF, and in other studies in CSF only (Table 2) [55,56 ▪ ,57,58]. However, these studies are very heterogenous, and mostly made use of bulk Sanger sequencing.…”
Section: Hiv Drug Resistance and Compartmentalization In Central Nerv...mentioning
confidence: 99%